Being Sad Is Not Always Bad: The Influence of Affect on Expository Text Comprehension. Issue 2 (17th February 2019) - Mills, Caitlin; Wu, Jennifer; D'Mello, Sidney
ABSTRACT: We investigated how affective states influence expository text comprehension and whether text valence moderates the effects (i.e., mood congruency). In Experiment 1 participants were randomly assigned to a happy or sad affective state (elicited via films) before reading a positive or negative version of a scientific text on animal adaptations. Participants ( n = 79) in the sad (film) group had higher scores on deep-reasoning ( d = .312) but not surface-level questions on a subsequent multiple-choice comprehension assessment; there was also no evidence for mood congruence. Using a neutral version of the same text, in Experiment 2 participants ( n = 52) in a fearful condition performed better on surface-level comprehension questions ( d = .594) compared with a sad condition, but the groups were on par for deep-reasoning questions. Experiment 3 ( n = 595) did not replicate the findings from Experiment 2 (no comprehension differences between the sad and fear groups) and there were no differences between the fear and happy groups. However, the sad group outperformed the happy group on deep-reasoning questions ( d = .210), thereby replicating Experiment 1. The overall findings were confirmed after pooling the data from the three experiments to increase power.